Potret Perkembangan Emosional Anak Usia Dini Di Keluarga Brokenhome di Wilayah Pati - Siti Fatimatuzzahroh; Laili Zumrotul Badriyah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
In the family, an atmosphere of harmonious relations between parents and children is needed because harmony in the household greatly influences the growth and development and education of children. But in reality it has become human nature that happiness, misery, suffering, joy, sorrow, harmony, harmony and conflict are events that always come and go in human life. This study aims to describe the impact of divorce on children's psychological development. With this type of literature review research, the authors explain that it is not the end of the husband and wife relationship, but divorced parents must still think about the further development and education of their children because divorce does not only have an impact on husband and wife but the biggest impact is the psychological development of children. The findings of this study are that divorce has a negative impact on the psychological development of children, because in general the psychological development of children whose parents are divorced is very disturbed, besides that the negative impact of divorce is the lack of love and attention from both parents. Household integrity is needed to help the development of psychology and children's education. Lack of attention and affection for children towards the divorce of the child's parents causes feelings of anxiety, confusion, restlessness, shame and sadness. Especially for teenagers, children will experience emotional disturbances and will run into juvenile delinquency and drugs